Cultural Powerful Youth: Interconnection of Local Wisdom and Cultural Industries through the MIC Strategy at the Sekaten Ceremony - Rahma, Fadilah Annisa (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
Maximizing the cultural potential exists in the DIY region,especially Kraton as a culture-based tourist destination, requires collaboration between government, private sector and local communities. Media Communication as a alternative pillar for developing the promotion of culture to the international to penetrate imaginary cultural boundaries. (Mele,Cantoni,2017). The elements of tourist destinations Kraton are quite complete,friendliness,full-value and upholding local culture are the main attractions for local and international tourists. Through the good cooperation,The Sekaten ceremony will stand strong amidst the onslaught of foreign culture by empowering youth, because it has great potential cultural sector in the digital era.The strategy in this research uses integrated marketing communications (IMC) by combining advertising,direct sales marketing,public relation and digital marketing. This research aimed to find out the potential of youth in cultural promotion and developing it in the challenges of modern era to international.Using literature search methods and direct interviews studies,this research presents data integrated between creative and cultural industries. The results of this research show that youth agents are not only connoisseurs of the cultural market,but more than that; who have penetrated the boundaries of unconsciousness the hyperreality stage and initiated the birth of creative cultural industry